CXCR4-targeted lipid-coated PLGA nanoparticles deliver sorafenib and overcome acquired drug resistance in liver cancer. (October 2015) - Gao, Dong-Yu; Lin, Ts-Ting; Sung, Yun-Chieh; Liu, Ya Chi; Chiang, Wen-Hsuan; Chang, Chih-Chun; Liu, Jia-Yu; Chen, Yunching
Abstract: Sorafenib, a multikinase inhibitor, has been used as an anti-angiogenic agent against highly vascular hepatocellular carcinoma (HCC) – yet associated with only moderate therapeutic effect and the high incidence of HCC recurrence. We have shown intratumoral hypoxia induced by sorafenib activated C-X-C receptor type 4 (CXCR4)/stromal-derived factor 1α (SDF1α) axis, resulting in polarization toward a tumor-promoting microenvironment and resistance to anti-angiogenic therapy in HCC. Herein, we formulated sorafenib in CXCR4-targeted lipid-coated poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) modified with a CXCR4 antagonist, AMD3100 to systemically deliver sorafenib into HCC and sensitize HCC to sorafenib treatment. We demonstrated that CXCR4-targeted NPs efficiently delivered sorafenib into HCCs and human umbilical vein endothelial cells (HUVECs) to achieve cytotoxicity and anti-angiogenic effect in vitro and in vivo . Despite the increased expression of SDF1α upon the persistent hypoxia induced by sorafenib-loaded CXCR4-targeted NPs, AMD3100 attached to the NPs can block CXCR4/SDF1α, leading to the reduced infiltration of tumor-associated macrophages, enhanced anti-angiogenic effect, a delay in tumor progression and increased overall survival in the orthotopic HCC model compared with other control groups. In conclusion, our results highlight the clinical potential of CXCR4-targeted NPs for delivering sorafenib and overcoming acquired drug resistance in liver cancer.